2018
DOI: 10.1186/s12879-018-3368-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNA-146a and miRNA-155 in gastritis induced by Helicobacter pylori infection in paediatric patients, adults, and an animal model

Abstract: BackgroundHelicobacter pylori is a major aetiologic agent associated with gastritis. H. pylori infections increase the expression of the Toll-like receptor (TLR), which in turn modulates the expression of microRNA (miRNA)-146a and miRNA-155. The objective of this study was to compare the expression of miRNA-146a and miRNA-155 in gastric lesions of paediatric and adult patients with different pathologies and in Mongolian gerbils (Meriones unguiculatus) infected with H. pylori 26,695.MethodsQuantification of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…A recent study revealed the upregulation of miR-146a and miR-155 in patients with gastritis induced by H. pylori infection[13], with the similar findings demonstrated by another research group[14]. Cortés-Márquez et al[14] further grouped the patients with gastritis by age, and found that both children and adults with H. pylori -induced gastritis displayed higher levels of miR-145a and miR-155. Moreover, the cancerization tendency of H. pylori -induced gastritis was correlated with the upregulation of miR-146a and miR-155[13,14].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…A recent study revealed the upregulation of miR-146a and miR-155 in patients with gastritis induced by H. pylori infection[13], with the similar findings demonstrated by another research group[14]. Cortés-Márquez et al[14] further grouped the patients with gastritis by age, and found that both children and adults with H. pylori -induced gastritis displayed higher levels of miR-145a and miR-155. Moreover, the cancerization tendency of H. pylori -induced gastritis was correlated with the upregulation of miR-146a and miR-155[13,14].…”
Section: Introductionsupporting
confidence: 55%
“…MiRNAs have no ability to encode proteins, but contribute to the modulation of gene expression[11,12]. A recent study revealed the upregulation of miR-146a and miR-155 in patients with gastritis induced by H. pylori infection[13], with the similar findings demonstrated by another research group[14]. Cortés-Márquez et al[14] further grouped the patients with gastritis by age, and found that both children and adults with H. pylori -induced gastritis displayed higher levels of miR-145a and miR-155.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…miRNA-146a and miRNA-155 have been described as downregulated in GC (Hou et al, 2012;Li et al, 2012), but also as a potential oncogenes in vitro (Shomali et al, 2017;Qu et al, 2018). Cortés-Márquez et al (2018) described higher gastric expression in both miRNAs in children, especially in those with severe gastritis, as observed in adults and in animal models. Because their role in carcinogenesis is controversial, further studies are needed to determine the potential role of overexpression among infected children.…”
Section: Micro Rnasmentioning
confidence: 97%
“…MiRNA‐155 is a crucial regulator of innate immunity and is expressed in a variety of immune cells during the inflammatory response. Cortes‐Marquez et al analyzed for the first time the expression of miRNAs associated with H pylori infection in pediatric patients. The results showed that increased expression of miRNA‐146a and miRNA‐155 was associated with the duration and outcome of H pylori infection, suggesting that different expression of miRNAs is indicative of the chronicity of infection and disease severity.…”
Section: Pathophysiologymentioning
confidence: 99%